Breast-sharing Technique in a Unilateral Mastectomy Patient. Issue 11 (November 2018) - Geerards, Daan; Kroeze, Alexander J.; Kroeze, Vincent J.; Broekhuysen, Coralien L.
Abstract : Summary: Breast reconstruction patients frequently desire consecutive or simultaneous contralateral breast reduction. When combining the requirements of both autologous breast reconstruction with symmetrizing breast reduction, a 2-staged contralateral pedicled breast sharing is a dignified alternative. We present a 60-year-old woman with a radical mastectomy and adjuvant radiotherapy. On the contralateral side, she had a hypertrophic breast with a desire for reduction mammaplasty. A 2-stage procedure for breast sharing was planned. A preoperative computed tomography scan, to assess the status of the fourth intercostal mammary perforator (IMAP), was performed. After the first procedure, symmastia was evident. Water-assisted liposuction and quilting sutures to the sternal periosteum were applied in a second procedure to correct the symmastia. We preserved the fourth intercostal perforator to provide optimal vascularization. Water-assisted liposuction and quilting sutures were used to correct the remaining symmastia and contributed to the aesthetics of both breasts. A drawback of this procedure is the need for multiple stages. Furthermore, oncological safety should be considered and surgeons should be aware of the risk for venous congestion. Breast-sharing could be a feasible alternative reconstruction for women seeking unilateral breast reconstruction with contralateral breast hypertrophy. It reduces the need for free-flap surgery and subsequent donor-site morbidity. Considering the fact that the contralateral breast must be of significant size, the indication for this type of reconstruction is limited.